Sharpening the mesowear tool: geometric morphometric analysis of cusp shape and diet in ruminants - Mihlbachler, Matthew C.; Barrón-Ortiz, Christina I.; Rankin, Brian D.; Theodor, Jessica M. (Frontiers in Ecology and Evolution, 2023)
Mesowear is a dietary proxy that relates attritive wear and abrasive wear to the shape of worn tooth cusps of ungulates. Traditional mesowear methods categorize cusps according to relief and sharpness. A geometric morphometric approach has the potential to measure shape with higher precision and to discover unrecognized aspects of cusp shape, possibly improving the efficacy of mesowear. We quantified mesowear in extant Ruminantia, using a 2-D semilandmark outline technique on upper second molar metacones generated from photographs. Among the 91 species sampled, 65 were preassigned to dietary categories, browser, grazer, mixed feeder, and frugivore based on substantiated documentation of diet in the wildlife literature. Metacone cusp shape and metacone mesowear score were found to be independent of size. Principal component and discriminant function analyses of Procrustes transformed semilandmark coordinates revealed two diet-related components of cusp shape. The primary component is related to the traditional mesowear variables of cusp height and side steepness. The secondary shape component reveals variation in the mesiodistal symmetry of the metacone and may relate to a proal vector during the power stroke phase or the relative orientation of the cusps with respect to the chewing stroke vector. Discriminant function analysis of semilandmark data accurately classified the diets of species more frequently (67.2%) than the traditional mesowear method (56.1%). The semilandmark data successfully recognized the diets of grazing and browsing species with correct classification rates ranging from 69%-95%. The diets of frugivorous and mixed feeding species were less frequently correctly recognized (33%-53%). Mixed feeding diets may be more difficult to recognize due to more heterogeneous diets when compared to browsers and grazers. Frugivores are more difficult to recognize because their rounded cusp apices resemble those of mixed feeders and grazers. We conclude that quantitative shape analysis improves the potential of mesowear. When used as a dietary proxy, we anticipate that mesowear analysis will correctly categorize the diets of most species. When misclassifications are made, they may most often be misclassifications of generalist mixed feeders and frugivores as either browsers or grazers.